Accidental button battery ingestion presenting as croup. Issue 3 (March 2014) - Gohil, R; Culshaw, J; Jackson, P; Singh, S
Abstract Objectives: To report a case of misdiagnosis of an impacted oesophageal button battery in a child, and to describe the associated risk factors for impaction and the management of such cases. Case report: An 18-month-old, otherwise fit and well child with stridulous respiration was initially treated for croup. Medical treatment over the course of three months failed, and appropriate imaging subsequently demonstrated an impacted button battery in the upper oesophagus. This was promptly removed. There were no signs of damage on direct visualisation, or on a follow-up contrast swallow image. Conclusion: This case highlights the difficulty of diagnosing oesophageal foreign bodies. We also discuss the characteristics of button batteries which confer a greater risk of impaction, and the associated sequelae and complications.